#TITLE_ALTERNATIVE# - SARI (NIM 15105008); Pembimbing: Dr. Irwan Meilano ST, MSc., dan Heri Andreas, ST, MT., SILFIANITA
Lembang Fault is one of the potential active faults located in Bandung . According to the Direktorat Tata Lingkungan Geologi dan Kawasan Pertambangan (DTLGKP), Lembang faultÃ‚Â’s earthquake will be cycled in every five hundred years. By looking at the correlation between fault length and earthquake magnitude directly, an earthquake caused by the fault could range about 6.5 SR. Therefore, to minimize the worst effect of the earthquake, we used to monitoring the activity level of the Lembang fault. Monitoring conducted to collect data fault symptoms, which used to analyze deformation on Lembang fault geometrically. Monitoring method implemented through the GPS survey conducted periodically. GPS survey carried out by using the relative (differential) positioning. Deformation analysis is conducted Geometrically, providing quantitative information to determine direction, dimension and movement of the model deformation. Analysis geometric of deformation is divided into 3, analysis of the displacement, estimated slip rate and strain analysis.